A ceramic aluminum-based silicon carbide layered composite material and a preparation method thereof

By using casting molding method and technical means of adding toughened phase, carbon fiber and LZ ceramic powder in ceramic aluminum-based silicon carbide layered composite materials, the problems of large brittleness and insufficient interface bonding strength are solved, and the fracture of the material is significantly improved Toughness and strength.

CN119035053BActive Publication Date: 2025-02-21广州众山功能材料有限公司 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411533579.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-21
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The existing ceramic aluminum-based silicon carbide layered composite materials have problems such as high brittleness and insufficient interface bonding strength, which affects its toughness and performance stability.

Method used

The layered composite material of aluminum matrix-first ceramic layer-aluminum-based silicon carbide layer-second ceramic layer was prepared by casting molding method, and the toughening phase, carbon fiber and LZ ceramic were added to the ceramic layer and the aluminum-based silicon carbide layer. The powder is chemically and mechanically treated to improve the interface bond strength and the fracture toughness of the material.

Benefits of technology

It effectively improves the fracture toughness and strength of the composite material, enhances the interface bonding force, and improves the high-temperature oxidation resistance and stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119035053B_ABST
    Figure CN119035053B_ABST
Patent Text Reader

Abstract

The present invention provides a ceramic aluminum-based silicon carbide layered composite material and a preparation method thereof, which relates to the technical field of aluminum-based composite materials, and comprises the following steps: S1: preparing a first ceramic slurry, coating the first ceramic slurry on the surface of an aluminum substrate, sintering through a first pretreatment, and obtaining a first ceramic layer; S2: chemically treating and / or mechanically treating the surface of the first ceramic layer; S3: preparing an aluminum-based silicon carbide slurry, coating the aluminum-based silicon carbide slurry on the surface of the first ceramic layer, sintering in an atmosphere protection, and obtaining an aluminum-based silicon carbide layer; S4: preparing a second ceramic slurry, coating the second ceramic slurry on the aluminum-based silicon carbide layer, sintering through a second pretreatment, and obtaining a second ceramic layer; and cooling to obtain a ceramic aluminum-based silicon carbide layered composite material. The layered composite material prepared by the present invention can effectively improve the fracture toughness and strength of the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum-based composite materials, and in particular to a ceramic aluminum-based silicon carbide layered composite material and a preparation method thereof. Background Art

[0002] Laminated composites are composite materials composed of multiple layers of different materials with excellent properties and characteristics. Common laminated composites in the prior art include composites of ceramic layers and aluminum-based silicon carbide layers, which are typical metal-based composites with aluminum or aluminum alloy as the matrix and silicon carbide particles, whiskers or fibers as the reinforcement phase. This composite material combines the good processing properties of metals with the high-temperature strength, hardness and wear resistance of ceramics. This composite material has the following advantages:

[0003] Excellent high-temperature performance: Both the ceramic layer and the aluminum-based silicon carbide layer have good high-temperature stability and heat resistance, making the composite material perform well in high-temperature environments;

[0004] Strong corrosion resistance: The ceramic layer and aluminum-based silicon carbide layer have good corrosion resistance, which makes the composite material have a long service life in harsh environments;

[0005] High strength and hardness: The aluminum-based silicon carbide layer has high strength and hardness, which can enhance the overall performance of the composite material.

[0006] However, layered composites with ceramic layers and aluminum-based silicon carbide layers also have some disadvantages:

[0007] Brittleness: The ceramic layer is highly brittle and easily breaks when impacted or bent, which reduces the toughness of the composite material.

[0008] Insufficient interface bonding strength: The interface bonding strength between the ceramic layer and the aluminum-based silicon carbide layer may be insufficient, and interface peeling is prone to occur, affecting the performance stability of the composite material.

[0009] Therefore, when designing and preparing layered composite materials with ceramic layers and aluminum-based silicon carbide layers, it is necessary to comprehensively consider the properties and defects of the materials in order to give full play to their advantages and overcome their disadvantages in specific application fields. Summary of the invention

[0010] The purpose of the present invention is to provide a ceramic aluminum-based silicon carbide layered composite material and a preparation method thereof. By adopting a tape casting method, a layered composite material of an aluminum matrix-a first ceramic layer-aluminum-based silicon carbide layer-a second ceramic layer is prepared, so that the prepared ceramic layer and the aluminum-based silicon carbide layer are relatively thin, and a multilayer composite material can be prepared according to production requirements, effectively improving the fracture toughness and strength of the composite material.

[0011] In order to achieve the above object, the present invention adopts the following technical solutions:

[0012] The present invention provides a method for preparing a ceramic aluminum-based silicon carbide layered composite material, comprising the following steps:

[0013] S1: preparing a first ceramic slurry, coating the first ceramic slurry on the surface of an aluminum substrate, and sintering the slurry through a first pretreatment to obtain a first ceramic layer;

[0014] The first ceramic slurry comprises: a toughening phase, silicon carbide, carbon fiber, an organic plasticizer, a dispersant, a binder, a coupling agent and a lubricant;

[0015] S2: chemically and mechanically treating the surface of the first ceramic layer;

[0016] S3: preparing an aluminum-based silicon carbide slurry, coating the aluminum-based silicon carbide slurry on the surface of the first ceramic layer, first pre-oxidizing it in an oxygen atmosphere, and then performing atmosphere protection sintering in a nitrogen atmosphere to obtain an aluminum-based silicon carbide layer;

[0017] The aluminum-based silicon carbide slurry comprises: silicon carbide, aluminum alloy powder, organic plasticizer, dispersant, binder, coupling agent and lubricant;

[0018] S4: preparing a second ceramic slurry, coating the second ceramic slurry on the aluminum-based silicon carbide layer, sintering through a second pretreatment to obtain a second ceramic layer; and obtaining a ceramic aluminum-based silicon carbide layered composite material after cooling;

[0019] The second ceramic slurry comprises: LZ ceramic powder, silicon carbide, carbon fiber, organic plasticizer, dispersant, binder, coupling agent and lubricant.

[0020] Further, based on the above technical solution, in step S1, the first ceramic slurry includes the following components by mass percentage:

[0021] Toughening phase 40-55%, silicon carbide 10-15%, carbon fiber 10-15%, organic plasticizer 3-10%, dispersant 5-10%, binder 2-5%, coupling agent 3-10% and lubricant 1-3%;

[0022] The toughening phase comprises alumina or YSZ, preferably YSZ;

[0023] And / or, in step S3, the aluminum-based silicon carbide slurry includes the following components by mass percentage:

[0024] Silicon carbide 35-50%, aluminum alloy powder 20-30%, organic plasticizer 5-15%, dispersant 5-10%, binder 5-15%, coupling agent 3-10% and lubricant 1-3%;

[0025] And / or, in step S4, the second ceramic slurry comprises the following components by mass percentage:

[0026] LZ ceramic powder 40-55%, silicon carbide 10-15%, carbon fiber 10-15%, organic plasticizer 3-10%, dispersant 5-10%, binder 2-5%, coupling agent 3-10% and lubricant 1-3%.

[0027] Further, based on the above technical solution, the particle size of the aluminum alloy powder is 1-10µm;

[0028] The aluminum alloy powder is selected from one of the models ZL107, ZL110, ZL104 or ZL305;

[0029] And / or, the particle size of the silicon carbide particles is 0.5-5 μm;

[0030] and / or, the particles of the LZ ceramic powder are 1-10 µm;

[0031] And / or, the organic plasticizer includes one or more of PVA, DBP, PVB, and diethylene glycol acetate;

[0032] And / or, the dispersant includes one or more of sodium metasilicate, sodium lauryl sulfate, sodium polyacrylate, and polyacrylamide;

[0033] And / or, the binder includes one or more of PVA, CMC, HEC, and PVP;

[0034] And / or, the coupling agent includes one or more of 3-methoxypropyltrimethoxysilane and isobutyltriethoxysilane;

[0035] And / or, the lubricant includes one or more of paraffin, PTFE, and oleic acid.

[0036] Further, based on the above technical solution, in step S1, the first pretreatment includes: at a pressure of 10-30 MPa, first heating to 600-650°C at a heating rate of 100-200°C / min, keeping the temperature for 5-10 minutes, and then cooling to room temperature at a cooling rate of 30-50°C / min;

[0037] And / or, in step S4, the second pretreatment includes: at a pressure of 5-10 MPa, first heating to 700-900°C at a heating rate of 3-20°C / min, keeping the temperature for 2-6 hours, and then cooling to room temperature at a cooling rate of 3-20°C / min.

[0038] Further, based on the above technical solution, in step S3, the atmosphere protection sintering includes: sintering the first ceramic layer coated with aluminum-based silicon carbide slurry at a temperature of 500-700° C. and a pressure of 10-20 MPa for 1-2 hours, and cooling with the furnace;

[0039] The pre-oxidation time is 1-2 hours, the temperature is 200-300° C., and the pressure is 10-20 MPa.

[0040] Further, based on the above technical solution, in step S2, the chemical treatment includes pickling treatment and silane coupling agent treatment;

[0041] The pickling treatment is: using hydrofluoric acid and / or concentrated nitric acid with a concentration of 0.5-1.5 mol / L to clean the surface of the first ceramic layer;

[0042] The silane coupling agent treatment comprises: coating the silane coupling agent on the surface of the first ceramic layer after pickling, and then curing;

[0043] The silane coupling agent includes one or more of 3-methoxypropyltrimethoxysilane and isobutyltriethoxysilane.

[0044] In step S2, the mechanical treatment includes surface grinding, sandblasting and cleaning.

[0045] Further, based on the above technical solution, in step S3, the preparation method of the aluminum-based silicon carbide slurry is as follows, by mass percentage:

[0046] S31: placing silicon carbide, an organic plasticizer, a binder, a coupling agent, and a lubricant in a solvent to obtain a mixed solution;

[0047] S32: placing the aluminum alloy powder and the dispersant in a mixed solution, and stirring at a rotation speed of 20000-30000 rpm to obtain a mixed slurry;

[0048] S33: ball milling the mixed slurry to obtain aluminum-based silicon carbide slurry.

[0049] Further, based on the above technical solution, in step S31, the solvent refers to polyethylene glycol and alcohol in a volume ratio of 1:(1-2);

[0050] and / or, the mass ratio of silicon carbide to solvent in step S31 is 1:(3-5);

[0051] And / or, the weight ratio of the mixed slurry to the grinding balls is 1:(8-10), and the ball milling time is 3-20 h.

[0052] Further, based on the above technical solution, the thickness of the first ceramic layer is 20-30 μm;

[0053] And / or, the thickness of the aluminum-based silicon carbide layer is 10-20 μm;

[0054] And / or, the second ceramic layer has a thickness of 20-30 μm.

[0055] The present invention also provides a ceramic aluminum-based silicon carbide layered composite material obtained by the preparation method of the ceramic aluminum-based silicon carbide layered composite material as described above.

[0056] The present invention provides a ceramic aluminum-based silicon carbide layered composite material and a preparation method thereof, and the beneficial effects are as follows:

[0057] 1. The present invention coats an aluminum-based silicon carbide layer on the surface of the ceramic layer containing the toughening phase to provide thermal insulation protection for the ceramic layer containing the toughening phase, effectively preventing the coating from cracking, and improving the high-temperature oxidation resistance and fracture toughness of the composite material.

[0058] 2. The present invention adds LZ ceramic powder to the second ceramic layer, the main component of which is pyrochlore type La2Zr2O7, whose thermal expansion coefficient is close to that of alumina. 3+ It can reduce the transformation rate of metastable θ-Al2O3 to stable α-Al2O3, reduce the residual stress, and inhibit the diffusion of cations in the aluminum-based silicon carbide layer, thereby ensuring the bonding force between the aluminum-based silicon carbide layer and the second ceramic layer.

[0059] 3. The present invention provides a layered composite material of an aluminum matrix-a first ceramic layer-aluminum-based silicon carbide layer-a second ceramic layer. By adopting a tape-casting method, the prepared ceramic layer and aluminum-based silicon carbide layer are relatively thin. Multilayer composite materials can be prepared according to production requirements, effectively improving the fracture toughness and strength of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0061] Figure 1 A schematic diagram of the structure of the ceramic aluminum-based silicon carbide layered composite material provided by the present invention;

[0062] icon:

[0063] 1. Aluminum substrate; 2. First ceramic layer; 3. Aluminum-based silicon carbide layer; 4. Second ceramic layer. DETAILED DESCRIPTION

[0064] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.

[0065] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0066] According to a first aspect of the present invention, there is provided a method for preparing a ceramic aluminum-based silicon carbide layered composite material, comprising the following steps:

[0067] S1: preparing a first ceramic slurry, coating the first ceramic slurry on the surface of an aluminum substrate, and sintering the slurry through a first pretreatment to obtain a first ceramic layer;

[0068] The first ceramic slurry comprises: a toughening phase, silicon carbide, carbon fiber, an organic plasticizer, a dispersant, a binder, a coupling agent and a lubricant;

[0069] S2: chemically and mechanically treating the surface of the first ceramic layer;

[0070] S3: preparing an aluminum-based silicon carbide slurry, coating the aluminum-based silicon carbide slurry on the surface of the first ceramic layer, first pre-oxidizing it in an oxygen atmosphere, and then performing atmosphere protection sintering in a nitrogen atmosphere to obtain an aluminum-based silicon carbide layer;

[0071] The aluminum-based silicon carbide slurry comprises: silicon carbide, aluminum alloy powder, organic plasticizer, dispersant, binder, coupling agent and lubricant;

[0072] S4: preparing a second ceramic slurry, coating the second ceramic slurry on the aluminum-based silicon carbide layer, sintering through a second pretreatment to obtain a second ceramic layer; and obtaining a ceramic aluminum-based silicon carbide layered composite material after cooling;

[0073] The second ceramic slurry comprises: LZ ceramic powder, silicon carbide, carbon fiber, organic plasticizer, dispersant, binder, coupling agent and lubricant.

[0074] Specifically, the present invention provides a layered composite material of an aluminum matrix-a first ceramic layer-aluminum-based silicon carbide layer-a second ceramic layer. By adopting a tape casting method, the prepared ceramic layer and aluminum-based silicon carbide layer are relatively thin. Multilayer composite materials can be prepared according to production requirements, effectively improving the fracture toughness and strength of the composite material.

[0075] Furthermore, the coating operation in the present invention is any one of spray coating, gravure roller coating, narrow coating or roller coating.

[0076] As an optional embodiment of the present invention, in step S1, the first ceramic slurry includes the following components by mass percentage:

[0077] Toughening phase 40-55% (such as 42%, 44%, 46%, 48%, 50%, 52%, etc.), silicon carbide 10-15% (such as 12%, 13%, 14%, etc.), carbon fiber 10-15% (such as 12%, 13%, 14%, etc.), organic plasticizer 3-10% (such as 4%, 5%, 6%, 7%, 8%, 9%, etc.), dispersant 5-10% (such as 6%, 7%, 8%, 9%, etc.), binder 2-5% (such as 3%, 4%, etc.), coupling agent 3-10% (such as 4%, 5%, 6%, 7%, 8%, 9%, etc.) and lubricant 1-3% (such as 1.5%, 2%, 2.5%, etc.);

[0078] The toughening phase comprises alumina or YSZ, preferably YSZ;

[0079] Specifically, the preparation method of the first ceramic slurry is: placing the components of the first ceramic slurry in a slurry agitator, setting the stirring rate to 15000 rpm, and the stirring time to 1 hour.

[0080] And / or, in step S3, the aluminum-based silicon carbide slurry includes the following components by mass percentage:

[0081] Silicon carbide 35-50% (such as 38%, 40%, 42%, 44%, 46%, 48%, etc.), aluminum alloy powder 20-30% (such as 22%, 24%, 26%, 28%, etc.), organic plasticizer 5-15% (such as 7%, 9%, 11%, 13%, etc.), dispersant 5-10% (such as 6%, 7%, 8%, 9%, etc.), binder 5-15% (such as 7%, 9%, 11%, 13%, etc.), coupling agent 3-10% (such as 4%, 5%, 6%, 7%, 8%, 9%, etc.) and lubricant 1-3% (such as 1.5%, 2%, 2.5%, etc.);

[0082] Specifically, the present invention stipulates that the content of silicon carbide must be greater than the content of aluminum alloy powder because if the content of aluminum alloy powder is higher than the content of silicon carbide, the Al element in the aluminum-based silicon carbide layer will diffuse faster, affecting the adhesion with the first ceramic layer and the second ceramic layer.

[0083] And / or, in step S4, the second ceramic slurry comprises the following components by mass percentage:

[0084] LZ ceramic powder 40-55% (such as 42%, 44%, 46%, 48%, 50%, 52%, etc.), silicon carbide 10-15% (such as 12%, 13%, 14%, etc.), carbon fiber 10-15% (such as 12%, 13%, 14%, etc.), organic plasticizer 3-10% (such as 4%, 5%, 6%, 7%, 8%, 9%, etc.), dispersant 5-10% (such as 6%, 7%, 8%, 9%, etc.), binder 2-5% (such as 3%, 4%, etc.), coupling agent 3-10% (such as 4%, 5%, 6%, 7%, 8%, 9%, etc.) and lubricant 1-3% (such as 1.5%, 2%, 2.5%, etc.).

[0085] Specifically, the preparation method of the second ceramic slurry is: placing the components of the second ceramic slurry in a slurry agitator, setting the stirring rate to 15000 rpm and the stirring time to 1 hour.

[0086] Specifically, YSZ is Y2O3 partially stabilized zirconium oxide (ZrO2), which is a typical rare earth-doped ZrO2 material. Due to its high thermal expansion coefficient, it is often used in various industries for surface thermal protection. However, YSZ is affected by the material properties of the zirconium oxide base itself. Under long-term high-temperature oxidation, thermal-mechanical coupling shock and thermal corrosion environments, the YSZ coating is prone to severe interface oxidation damage and organizational structure changes, resulting in changes in the thermal and mechanical properties of the coating, inducing problems such as interlayer delamination and decreased thermal insulation performance.

[0087] The present invention coats an aluminum-based silicon carbide layer on the surface of the ceramic layer containing YSZ to provide heat insulation protection for the ceramic layer containing YSZ, effectively prevent cracking of the coating, and improve the high-temperature oxidation resistance and fracture toughness of the composite material.

[0088] In the aluminum-based silicon carbide layer, silicon carbide has a low thermal expansion coefficient, which can match the higher thermal expansion coefficient of YSZ, thereby reducing thermal stress and effectively reducing the oxidation rate of silicon carbide and YSZ. In addition, silicon carbide will be oxidized in a high temperature environment to form a SiO2 film, which can further prevent the oxidation of YSZ and improve the protection of the ceramic layer containing YSZ.

[0089] In addition, the carbon fibers in the first ceramic layer or the second ceramic layer and silicon carbide can be combined together to form a silicon carbide matrix containing carbon fibers after sintering under atmosphere protection, which can not only strengthen the bonding strength between the first ceramic layer and the aluminum-based silicon carbide layer and improve the stability of the composite material, but also introduce Y2O3 into the silicon carbide containing carbon fibers, effectively improving the density and uniformity of silicon carbide. At the same time, Y2O3 can react with SiO2 generated by oxidation of silicon carbide in an oxygen atmosphere to form Y2Si2O7 with low volatility and oxygen permeability, thereby effectively improving the fracture toughness, corrosion resistance and oxidation resistance of the composite material.

[0090] In the aluminum-based silicon carbide layer, the Al element in the aluminum alloy powder can produce an aluminum oxide anti-oxidation layer to further protect the base YSZ from high-temperature oxidation. Aluminum oxide can also effectively improve the fracture toughness, stability, wear resistance and thermal shock resistance of the layered composite material.

[0091] Pyrochlore-type La2Zr2O7-based materials have become popular ceramic materials for high-performance thermal protective coatings due to their low thermal conductivity, low oxygen ion conductivity, and excellent high-temperature phase structure stability.

[0092] In the present invention, LZ ceramic powder is added to the second ceramic layer, and its main component is pyrochlore type La2Zr2O7, whose thermal expansion coefficient is close to that of alumina. 3+ It can reduce the transformation rate of metastable θ-Al2O3 to stable α-Al2O3, reduce the residual stress, and inhibit the diffusion of cations in the aluminum-based silicon carbide layer, ensuring the bonding force between the aluminum-based silicon carbide layer and the second ceramic layer;

[0093] In addition, La2Zr2O7 further alleviates the difference in thermal expansion coefficient with the underlying YSZ coating, thereby extending the high-temperature thermal cycle life of the entire coating.

[0094] As an optional embodiment of the present invention, the particle size of the aluminum alloy powder is 1-10µm (such as 2µm, 4µm, 6µm, 8µm, etc.);

[0095] Preferably, the aluminum alloy powder is selected from one of the models ZL107, ZL110, ZL104 or ZL305;

[0096] Specifically, the aluminum alloy powder contains a small amount of Cu and Mg, which can effectively reduce the interface reaction and improve the wettability between SiC and Al, and improve the adhesion between the first ceramic layer, the second ceramic layer and the aluminum-based silicon carbide layer.

[0097] and / or, the particle size of the silicon carbide particles is 0.5-5 μm, such as 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, etc.);

[0098] and / or, the LZ ceramic powder has a particle size of 1-10 µm (e.g., 2 µm, 4 µm, 6 µm, 8 µm, etc.);

[0099] And / or, the organic plasticizer includes one or more of PVA, DBP, PVB, and diethylene glycol acetate;

[0100] And / or, the dispersant includes one or more of sodium metasilicate, sodium lauryl sulfate, sodium polyacrylate, and polyacrylamide;

[0101] And / or, the binder includes one or more of PVA, CMC, HEC, and PVP;

[0102] And / or, the coupling agent includes one or more of 3-methoxypropyltrimethoxysilane and isobutyltriethoxysilane;

[0103] And / or, the lubricant includes one or more of paraffin, PTFE, and oleic acid.

[0104] As an optional embodiment of the present invention, in step S1, the first pretreatment includes: at a pressure of 10-30MPa (such as 12MPa, 14MPa, 16MPa, 18MPa, 20MPa, 22MPa, 24MPa, 26MPa, 28MPa, etc.), first heating to 600-650°C (such as 610°C, 620°C, 630°C, 640°C, etc.) at a heating rate of 100-200°C / min (such as 120°C / min, 140°C / min, 160°C / min, 180°C / min, etc.), keeping warm for 5-10min (such as 6min, 7min, 8min, 9min, etc.), and then cooling to room temperature at a cooling rate of 30-50°C / min (such as 35°C / min, 40°C / min, 45°C / min, etc.);

[0105] And / or, in step S4, the second pretreatment includes: under a pressure of 5-10MPa (such as 6MPa, 7MPa, 8MPa, 9MPa, etc.), first heating to 700-900℃ (such as 720℃, 740℃, 760℃, 780℃, 800℃, 820℃, 840℃, 860℃, 880℃, etc.) at a heating rate of 3-20℃ / min (such as 5℃ / min, 7℃ / min, 10℃ / min, 12℃ / min, 15℃ / min, 17℃ / min, etc.), keeping it for 2-6h (such as 3h, 4h, 5h, etc.), and then cooling it to room temperature at a cooling rate of 3-20℃ / min (such as 5℃ / min, 10℃ / min, 15℃ / min, etc.).

[0106] By reasonably controlling the parameters of hot pressing or pretreatment, the present invention can ensure that the ceramic layer has sufficient toughness and plasticity during the sintering process, and at the same time is tightly bonded with the aluminum-based silicon carbide layer of the substrate, effectively reducing the internal defects of the ceramic layer, and improving its density and bonding strength, so that the prepared ceramic layer has excellent performance and stability.

[0107] Furthermore, in the second pretreatment, the pretreatment temperature needs to be strictly controlled at 700-900°C. This is because if the temperature is too high, the Al element of the formed alumina-silicon dioxide layer will diffuse outward and react chemically with La2Zr2O7 to form an unstable LaAlO3 new phase, forming an intermediate layer, causing the volume of the composite material to shrink and the porosity in the surface layer to increase, affecting the adhesion between the second ceramic layer and the aluminum-based silicon carbide layer, causing the second ceramic layer to easily peel off.

[0108] As an optional embodiment of the present invention, in step S3, the atmosphere protection sintering includes: sintering the first ceramic layer coated with aluminum-based silicon carbide slurry at a temperature of 500-700°C (such as 550°C, 600°C, 650°C, etc.) and a pressure of 10-20MPa (such as 12MPa, 14MPa, 16MPa, 18MPa, etc.) for 1-2h, and cooling with the furnace;

[0109] The pre-oxidation time is 1-2h (such as 1.2h, 1.4h, 1.6h, 1.8h, etc.), the temperature is 200-300°C (such as 220°C, 240°C, 260°C, 280°C, etc.), and the pressure is 10-20MPa (such as 12MPa, 14MPa, 16MPa, 18MPa, etc.).

[0110] Specifically, step S3 is sintered in a tube furnace. Pre-oxidation is performed first because only by sintering in an oxygen atmosphere can a SiO2 film be formed, which can further prevent YSZ oxidation and improve the protection of the ceramic layer containing YSZ. Furthermore, SiO2 can react with Y2O3 in an oxygen atmosphere to generate Y2Si2O7 with low volatility and oxygen permeability, thereby effectively improving the fracture toughness, corrosion resistance and oxidation resistance of the composite material.

[0111] As an optional embodiment of the present invention, in step S2, the chemical treatment includes pickling treatment and silane coupling agent treatment;

[0112] The pickling treatment is: using hydrofluoric acid and / or concentrated nitric acid with a concentration of 0.5-1.5 mol / L to clean the surface of the first ceramic layer;

[0113] Specifically, the purpose of pickling is to remove organic matter, grease, dust and other impurities on the ceramic surface, providing a clean surface for subsequent coating. Pickling can also form micro-roughness on the surface of the first ceramic layer and increase the surface area, thereby improving the bonding strength between the first ceramic layer and the aluminum-based silicon carbide layer.

[0114] The silane coupling agent treatment comprises: coating the silane coupling agent on the surface of the first ceramic layer after pickling, and then curing;

[0115] Preferably, the silane coupling agent includes one or more of 3-methoxypropyltrimethoxysilane and isobutyltriethoxysilane.

[0116] Specifically, the purpose of using silane coupling agent for treatment is: since the silane coupling agent contains two different functional groups, one end can react with the hydroxyl group on the ceramic surface to form a covalent bond, and the other end can form a chemical bond with the aluminum-based silicon carbide layer, thereby establishing a strong chemical bond between the ceramic layer and the aluminum-based silicon carbide layer; the silane coupling agent can also improve the wettability of the ceramic surface, so that the aluminum-based silicon carbide layer can better wet the ceramic surface, improve the uniformity of the aluminum-based silicon carbide layer and the adhesion of the ceramic layer.

[0117] In step S2, the mechanical treatment includes surface grinding, sandblasting and cleaning.

[0118] Specifically, the surface grinding includes: using a grinding tool to lightly grind the surface of the ceramic layer to increase the surface roughness, which is beneficial to enhance the mechanical locking between the ceramic layer and other layers;

[0119] The sandblasting treatment includes using sandblasting equipment to sandblast the surface of the ceramic layer to form a microscopic concave-convex structure and improve the surface roughness and adhesion;

[0120] The cleaning process includes: cleaning the surface with alcohol to remove impurities and residues generated during grinding or sandblasting.

[0121] As an optional embodiment of the present invention, in step S3, the preparation method of the aluminum-based silicon carbide slurry is as follows, by mass percentage:

[0122] S31: placing silicon carbide, an organic plasticizer, a binder, a coupling agent, and a lubricant in a solvent to obtain a mixed solution;

[0123] S32: placing the aluminum alloy powder and the dispersant in a mixed solution, and stirring at a rotation speed of 20000-30000 rpm to obtain a mixed slurry;

[0124] S33: ball-milling the mixed slurry, and obtaining aluminum-based silicon carbide slurry after drying.

[0125] As an optional embodiment of the present invention, in step S31, the solvent refers to polyethylene glycol and alcohol in a volume ratio of 1:(1-2) (such as 1:1, 1:2, etc.);

[0126] Specifically, the present invention uses a high content of alcohol as a solvent because the alcohol can reduce the viscosity and surface tension of the mixed slurry, so that the aluminum alloy powder and silicon carbide particles can be fully dispersed in the mixed slurry.

[0127] and / or, the mass ratio of silicon carbide to solvent in step S31 is 1:(3-5) (e.g., 1:3, 1:4, 1:5, etc.);

[0128] And / or, in step S33, the weight ratio of the mixed slurry to the grinding balls is 1:(8-10) (e.g., 1:8.5, 1:9, 1:9.5, etc.);

[0129] The ball milling time is 3-20 h.

[0130] As an optional embodiment of the present invention, the thickness of the first ceramic layer is 20-30 μm;

[0131] And / or, the thickness of the aluminum-based silicon carbide layer is 10-20 μm;

[0132] And / or, the second ceramic layer has a thickness of 20-30 μm.

[0133] Specifically, the present invention limits the thickness of the aluminum-based silicon carbide layer to be smaller than the first ceramic layer and the second ceramic layer because, if the thickness of the aluminum-based silicon carbide layer is larger, the diffusion of the Al element will be accelerated, affecting the adhesion with the first ceramic layer and the second ceramic layer.

[0134] According to a second aspect of the present invention, there is provided a ceramic aluminum-based silicon carbide layered composite material obtained by the method for preparing the ceramic aluminum-based silicon carbide layered composite material as described above.

[0135] Specifically, Figure 1 It is a schematic diagram of the structure of a ceramic aluminum-based silicon carbide layered composite material, which includes, from top to bottom, a second ceramic layer 4, an aluminum-based silicon carbide layer 3, a first ceramic layer 2 and an aluminum matrix 1.

[0136] The present invention will be further described in detail below with reference to specific embodiments and comparative examples.

[0137] It should be noted that, except for raw materials of certain limited types in the present invention, the remaining raw materials can be any commercially available type of commodity.

[0138] Example 1, S1: 55 kg of YSZ, 15 kg of silicon carbide (average particle size of 0.5 μm), 15 kg of carbon fiber, 10 kg of PVA, 10 kg of sodium metasilicate, 5 kg of CMC, 10 kg of 3-methoxypropyltrimethoxysilane and 3 kg of paraffin were placed in a slurry agitator, and the stirring rate was set to 15000 rpm for 1 hour to obtain a first ceramic slurry;

[0139] The first ceramic slurry is coated on the surface of the aluminum substrate, and the temperature is first increased to 600° C. at a heating rate of 100° C. / min under a pressure of 30 MPa, and then the temperature is reduced to room temperature at a cooling rate of 30° C. / min after being kept for 6 minutes, to obtain a first ceramic layer;

[0140] S2: using 1.5 mol / L hydrofluoric acid and concentrated nitric acid to clean the surface of the first ceramic layer; coating 3-methoxypropyltrimethoxysilane on the surface of the first ceramic layer after pickling, and then curing;

[0141] S3: 50 kg of silicon carbide (average particle size of 0.5 μm), 15 kg of PVA, 15 kg of CMC, 10 kg of 3-methoxypropyltrimethoxysilane and 3 kg of paraffin are placed in polyethylene glycol and alcohol in a volume ratio of 1:2 to obtain a mixed solution, the mixed solution is placed in a slurry agitator for stirring, and then 20 kg of ZL107 aluminum alloy powder (average particle size of 1 μm) and 10 kg of sodium metasilicate are added, and stirring is continued. The stirring rate is set to 20000 rpm and the stirring time is 2 hours to obtain a mixed slurry;

[0142] The mixed slurry was added into a rolling ball mill, alcohol was added as a medium, and ball milling was performed for 20 h, wherein the weight ratio of the mixed slurry to the grinding balls was 1:8; and aluminum-based silicon carbide slurry was obtained;

[0143] coating the aluminum-based silicon carbide slurry on the surface of the first ceramic layer;

[0144] First, pre-oxidation was performed in an oxygen atmosphere for 1 hour at a temperature of 200°C and a pressure of 10 MPa; then, the first ceramic layer coated with the aluminum-based silicon carbide slurry was sintered in a nitrogen atmosphere at a temperature of 600°C and a pressure of 20 MPa for 2 hours, and then cooled in the furnace;

[0145] S4: 55kg of LZ ceramic powder (average particle size of 1µm), 15kg of silicon carbide (average particle size of 0.5μm), 15kg of carbon fiber, 10kg of PVA, 10kg of sodium metasilicate, 5kg of CMC, 10kg of 3-methoxypropyltrimethoxysilane and 3kg of paraffin are placed in a slurry agitator, and the stirring rate is set to 15000rpm for 1h to obtain a second ceramic slurry. The second ceramic slurry is coated on the aluminum-based silicon carbide layer, and the temperature is first increased to 900°C at a heating rate of 20°C / min under a pressure of 10MPa, and after keeping the temperature for 6h, the temperature is then decreased to room temperature at a cooling rate of 20°C / min to obtain a second ceramic layer.

[0146] In this embodiment, a ceramic aluminum-based silicon carbide layered composite material of aluminum substrate-first ceramic layer-aluminum-based silicon carbide layer-second ceramic layer is prepared, and its performance test data is shown in Table 1.

[0147] Example 2, S1: 40 kg of YSZ, 10 kg of silicon carbide (average particle size of 5 μm), 10 kg of carbon fiber, 3 kg of DBP, 5 kg of sodium dodecyl sulfate, 2 kg of PVA, 3 kg of isobutyltriethoxysilane and 1 kg of PTFE were placed in a slurry agitator, and the stirring rate was set to 15000 rpm for 1 hour to obtain a first ceramic slurry;

[0148] The first ceramic slurry is coated on the surface of the aluminum substrate, and the temperature is first increased to 650°C at a heating rate of 150°C / min under a pressure of 10 MPa, and then the temperature is cooled to room temperature at a cooling rate of 50°C / min after being kept for 10 minutes, to obtain a first ceramic layer;

[0149] S2: using 0.5 mol / L hydrofluoric acid and concentrated nitric acid to clean the surface of the first ceramic layer; coating 3-methoxypropyltrimethoxysilane on the surface of the first ceramic layer after pickling, and then curing;

[0150] S3: 35 kg of silicon carbide (average particle size of 5 μm), 5 kg of DBP, 5 kg of PVA, 3 kg of isobutyl triethoxysilane and 1 kg of PTFE are placed in polyethylene glycol and alcohol in a volume ratio of 1:2 to obtain a mixed solution, the mixed solution is placed in a slurry agitator for stirring, and then 20 kg of ZL110 aluminum alloy powder (average particle size of 5 μm) and 5 kg of sodium dodecyl sulfate are added, and stirring is continued. The stirring rate is set to 20000 rpm and the stirring time is 2 hours to obtain a mixed slurry;

[0151] The mixed slurry was added into a rolling ball mill, alcohol was added as a medium, and ball milling was performed for 10 h, wherein the weight ratio of the mixed slurry to the grinding balls was 1:9; and aluminum-based silicon carbide slurry was obtained;

[0152] coating the aluminum-based silicon carbide slurry on the surface of the first ceramic layer;

[0153] First, pre-oxidation was performed in an oxygen atmosphere for 1 hour at a temperature of 200°C and a pressure of 10 MPa; then, the first ceramic layer coated with the aluminum-based silicon carbide slurry was sintered in a nitrogen atmosphere at a temperature of 700°C and a pressure of 10 MPa for 2 hours, and then cooled in the furnace;

[0154] S4: 40 kg of LZ ceramic powder (average particle size of 5 μm), 10 kg of silicon carbide (average particle size of 5 μm), 10 kg of carbon fiber, 3 kg of DBP, 5 kg of sodium dodecyl sulfate, 2 kg of PVA, 3 kg of isobutyl triethoxysilane and 1 kg of PTFE were placed in a slurry agitator, and the stirring rate was set to 15000 rpm for 1 hour to obtain a second ceramic slurry, and the second ceramic slurry was coated on the aluminum-based silicon carbide layer, and the temperature was first increased to 900°C at a heating rate of 5°C / min under a pressure of 5 MPa, and after keeping the temperature for 6 hours, the temperature was then decreased to room temperature at a cooling rate of 10°C / min to obtain a second ceramic layer;

[0155] In this embodiment, a ceramic aluminum-based silicon carbide layered composite material of aluminum substrate-first ceramic layer-aluminum-based silicon carbide layer-second ceramic layer is prepared, and its performance test data is shown in Table 1.

[0156] Example 3, S1: 45 kg of aluminum oxide, 12 kg of silicon carbide (average particle size of 2 μm), 13 kg of carbon fiber, 7 kg of organic plasticizer, 7 kg of dispersant, 3 kg of binder, 7 kg of coupling agent and 2 kg of lubricant were placed in a slurry agitator, and the stirring rate was set to 15000 rpm for 1 hour to obtain a first ceramic slurry;

[0157] The first ceramic slurry is coated on the surface of the aluminum substrate, and the temperature is first increased to 650°C at a heating rate of 200°C / min under a pressure of 20 MPa, and then the temperature is cooled to room temperature at a cooling rate of 40°C / min after being kept at the temperature for 5 minutes, to obtain a first ceramic layer;

[0158] S2: using 1 mol / L hydrofluoric acid and concentrated nitric acid to clean the surface of the first ceramic layer; coating 3-methoxypropyltrimethoxysilane on the surface of the first ceramic layer after pickling, and then curing;

[0159] S3: 45 kg of silicon carbide (average particle size of 2 μm), 12 kg of organic plasticizer, 13 kg of binder, 5 kg of coupling agent and 2 kg of lubricant are placed in polyethylene glycol and alcohol in a volume ratio of 1:2 to obtain a mixed solution, the mixed solution is placed in a slurry agitator for stirring, and then 25 kg of ZL104 aluminum alloy powder (average particle size of 8 μm) and 6 kg of dispersant are added, and stirring is continued. The stirring rate is set to 20000 rpm and the stirring time is 2 hours to obtain a mixed slurry;

[0160] The mixed slurry was added into a rolling ball mill, alcohol was added as a medium, and ball milling was performed for 15 hours, wherein the weight ratio of the mixed slurry to the grinding balls was 1:10; and aluminum-based silicon carbide slurry was obtained;

[0161] coating the aluminum-based silicon carbide slurry on the surface of the first ceramic layer;

[0162] First, pre-oxidation was performed in an oxygen atmosphere for 2 hours at a temperature of 200°C and a pressure of 10 MPa; then, the first ceramic layer coated with aluminum-based silicon carbide slurry was sintered in a nitrogen atmosphere at a temperature of 600°C and a pressure of 10 MPa for 1 hour, and then cooled in the furnace;

[0163] S4: 45 kg of LZ ceramic powder (average particle size of 3 µm), 12 kg of silicon carbide (average particle size of 2 µm), 13 kg of carbon fiber, 7 kg of organic plasticizer, 6 kg of dispersant, 4 kg of binder, 5 kg of coupling agent and 2 kg of lubricant are placed in a slurry agitator, and the stirring rate is set to 15000 rpm for 1 hour to obtain a second ceramic slurry, and the second ceramic slurry is coated on the aluminum-based silicon carbide layer, and the temperature is first increased to 800°C at a heating rate of 15°C / min under a pressure of 7 MPa, and after keeping the temperature for 4 hours, the temperature is then decreased to room temperature at a cooling rate of 15°C / min to obtain a second ceramic layer;

[0164] In this embodiment, a ceramic aluminum-based silicon carbide layered composite material of aluminum substrate-first ceramic layer-aluminum-based silicon carbide layer-second ceramic layer is prepared, and its performance test data is shown in Table 1.

[0165] Comparative Example 1

[0166] The main difference between this comparative example and Example 1 is that no toughening phase is added to the first ceramic slurry in this comparative example, and the remaining steps and operations are the same as those in Example 1.

[0167] Comparative Example 2

[0168] The main difference between this comparative example and Example 1 is that the first ceramic layer and the second ceramic layer do not contain silicon carbide, and the remaining steps and operations are the same as those in Example 1.

[0169] Comparative Example 3

[0170] The main difference between this comparative example and Example 1 is that the second ceramic layer does not contain LZ ceramic powder, and the remaining steps and operations are the same as those in Example 1.

[0171] Comparative Example 4

[0172] The main difference between this comparative example and Example 1 is that the content of aluminum alloy powder in the aluminum-based silicon carbide layer is greater than the content of silicon carbide, and the remaining steps and operations are the same as Example 1.

[0173] Comparative Example 5

[0174] The main difference between this comparative example and Example 1 is that the thickness of the coated aluminum-based silicon carbide layer is greater than the thickness of the first ceramic layer and the second ceramic layer, and the remaining steps and operations are the same as those in Example 1.

[0175] Comparative Example 6

[0176] The main difference between this comparative example and Example 1 is that in step S3, there is no pre-oxidation, and protective sintering is directly performed under a nitrogen atmosphere. The remaining steps and operations are the same as in Example 1.

[0177] The mechanical properties testing methods of the composite materials prepared in Examples 1-3 and Comparative Examples 1-6 are as follows:

[0178] Tensile test: The tensile test specimens of composite materials are processed according to the standard of GB / T228-2010 "Room Temperature Tensile Test of Metallic Materials", and the carbon fiber is ensured to be located in the center of the tensile sheet.

[0179] The tensile properties of the samples were tested using a DNS100 universal testing machine at a tensile speed of 1.2 mm / min.

[0180] Fracture toughness refers to GB / T 4161-2007 "Plane Strain Fracture Toughness K of Metallic Materials" IC "Test Methods".

[0181] Coating thickness: measured according to standard JC / T 2246-2014 "Fine ceramic coating thickness test method grinding pit method".

[0182] The mechanical properties of the composite materials prepared in Examples 1-3 and Comparative Examples 1-6 are shown in Table 1:

[0183] Table 1

[0184] Tensile strength MPa <![CDATA[Fracture toughness MPa·m 1 / 2 > Elongation at break % Thickness of the first ceramic layer μm Aluminum-based SiC layer thickness μm The thickness of the second ceramic layer μm Example 1 357 7.5 9.8 23 15 25 Example 2 329 6.5 9.4 20 10 20 Example 3 284 5.4 7.3 30 20 30 Comparative Example 1 167 2.3 4.2 25 12 22 Comparative Example 2 237 3.4 5.7 23 14 26 Comparative Example 3 267 4.3 6.2 28 13 28 Comparative Example 4 338 6.1 7.9 27 18 24 Comparative Example 5 305 5.8 7.3 22 30 26 Comparative Example 6 278 4.8 6.9 26 17 21

[0185] According to Table 1, compared with Example 1, since no toughening phase is added in Comparative Example 1, the strength of the first ceramic layer is significantly reduced, which affects the tensile strength and fracture toughness of the layered composite material.

[0186] According to Table 1, compared with Example 1, since the first ceramic layer and the second ceramic layer in Comparative Example 2 do not contain silicon carbide, the protective effect of the first ceramic layer containing YSZ is reduced, and it is also unable to synergize with the carbon fiber to enhance the adhesion between the layers, ultimately affecting the tensile strength and fracture toughness of the layered composite material.

[0187] According to Table 1, compared with Example 1, since the second ceramic layer in Comparative Example 3 does not contain LZ ceramic powder, the adhesion between the second ceramic layer and the aluminum-based silicon carbide layer is reduced, which affects the fracture toughness of the layered composite material.

[0188] According to Table 1, compared with Example 1, since the content of aluminum alloy powder in the aluminum-based silicon carbide layer in Comparative Example 4 is greater than the content of silicon carbide, the Al element in the aluminum-based silicon carbide layer is accelerated to diffuse, resulting in a decrease in the adhesion between the aluminum-based silicon carbide layer and the first ceramic layer and the second ceramic layer, respectively, affecting the fracture toughness of the layered composite material.

[0189] According to Table 1, compared with Example 1, since the thickness of the aluminum-based silicon carbide layer coated in Comparative Example 5 is greater than the thickness of the first ceramic layer and the second ceramic layer, the Al element in the aluminum-based silicon carbide layer is accelerated to diffuse, resulting in a decrease in the adhesion between the aluminum-based silicon carbide layer and the first ceramic layer and the second ceramic layer, respectively, affecting the fracture toughness of the layered composite material.

[0190] According to Table 1, compared with Example 1, since in step S3 of Comparative Example 6, there is no pre-oxidation and protective sintering is directly performed under a nitrogen atmosphere, SiO2 film cannot be generated, the protective effect of the ceramic layer containing YSZ is weakened, and Y2Si2O7 with low volatility and oxygen permeability cannot be generated, resulting in decreased tensile strength and fracture toughness of the layered composite material.

[0191] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a ceramic aluminum-based silicon carbide layered composite material, characterized in that: The steps include: S1: preparing a first ceramic slurry, coating the first ceramic slurry on the surface of an aluminum substrate, and sintering the slurry through a first pretreatment to obtain a first ceramic layer; The first ceramic slurry comprises: a toughening phase, silicon carbide, carbon fiber, an organic plasticizer, a dispersant, a binder, a coupling agent and a lubricant; S2: chemically and mechanically treating the surface of the first ceramic layer; S3: preparing an aluminum-based silicon carbide slurry, coating the aluminum-based silicon carbide slurry on the surface of the first ceramic layer, first pre-oxidizing it in an oxygen atmosphere, and then performing atmosphere protection sintering in a nitrogen atmosphere to obtain an aluminum-based silicon carbide layer; The aluminum-based silicon carbide slurry comprises: silicon carbide, aluminum alloy powder, organic plasticizer, dispersant, binder, coupling agent and lubricant; S4: preparing a second ceramic slurry, coating the second ceramic slurry on the aluminum-based silicon carbide layer, sintering through a second pretreatment to obtain a second ceramic layer; and obtaining a ceramic aluminum-based silicon carbide layered composite material after cooling; The second ceramic slurry comprises: LZ ceramic powder, silicon carbide, carbon fiber, organic plasticizer, dispersant, binder, coupling agent and lubricant.

2. The method for preparing the ceramic aluminum-based silicon carbide layered composite material according to claim 1, characterized in that: In step S1, the first ceramic slurry includes the following components by mass percentage: Toughening phase 40-55%, silicon carbide 10-15%, carbon fiber 10-15%, organic plasticizer 3-10%, dispersant 5-10%, binder 2-5%, coupling agent 3-10% and lubricant 1-3%; The toughening phase includes alumina or YSZ; And / or, in step S3, the aluminum-based silicon carbide slurry includes the following components by mass percentage: Silicon carbide 35-50%, aluminum alloy powder 20-30%, organic plasticizer 5-15%, dispersant 5-10%, binder 5-15%, coupling agent 3-10% and lubricant 1-3%; And / or, in step S4, the second ceramic slurry comprises the following components by mass percentage: LZ ceramic powder 40-55%, silicon carbide 10-15%, carbon fiber 10-15%, organic plasticizer 3-10%, dispersant 5-10%, binder 2-5%, coupling agent 3-10% and lubricant 1-3%.

3. The method for preparing the ceramic aluminum-based silicon carbide layered composite material according to claim 2, characterized in that: The particle size of the aluminum alloy powder is 1-10 μm; The aluminum alloy powder is selected from one of the models ZL107, ZL110, ZL104 or ZL305; And / or, the particle size of silicon carbide in the first ceramic slurry, the aluminum-based silicon carbide slurry and the second ceramic slurry is 0.5-5 μm; And / or, the particle size of the LZ ceramic powder is 1-10 μm; And / or, the organic plasticizers in the first ceramic slurry, the aluminum-based silicon carbide slurry, and the second ceramic slurry all include one or more of PVA, DBP, PVB, and diethylene glycol acetate; And / or, the dispersants in the first ceramic slurry, the aluminum-based silicon carbide slurry and the second ceramic slurry all include one or more of sodium metasilicate, sodium lauryl sulfate, sodium polyacrylate and polyacrylamide; And / or, the binders in the first ceramic slurry, the aluminum-based silicon carbide slurry, and the second ceramic slurry all include one or more of PVA, CMC, HEC, and PVP; And / or, the coupling agents in the first ceramic slurry, the aluminum-based silicon carbide slurry, and the second ceramic slurry all include one or more of 3-methoxypropyltrimethoxysilane and isobutyltriethoxysilane; And / or, the lubricants in the first ceramic slurry, the aluminum-based silicon carbide slurry, and the second ceramic slurry all include one or more of paraffin, PTFE, and oleic acid.

4. The method for preparing the ceramic aluminum-based silicon carbide layered composite material according to claim 1, characterized in that: In step S1, the first pretreatment includes: at a pressure of 10-30 MPa, heating to 600-650°C at a heating rate of 100-200°C / min, keeping the temperature for 5-10 minutes, and then cooling to room temperature at a cooling rate of 30-50°C / min; And / or, in step S4, the second pretreatment includes: at a pressure of 5-10 MPa, first heating to 700-900°C at a heating rate of 3-20°C / min, keeping the temperature for 2-6 hours, and then cooling to room temperature at a cooling rate of 3-20°C / min.

5. The method for preparing the ceramic aluminum-based silicon carbide layered composite material according to claim 1, characterized in that: In step S3, the atmosphere protection sintering includes: sintering the first ceramic layer coated with aluminum-based silicon carbide slurry at a temperature of 500-700° C. and a pressure of 10-20 MPa for 1-2 hours, and cooling with the furnace; The pre-oxidation time is 1-2 hours, the temperature is 200-300° C., and the pressure is 10-20 MPa.

6. The method for preparing the ceramic aluminum-based silicon carbide layered composite material according to claim 1, characterized in that: In step S2, the chemical treatment includes pickling treatment and silane coupling agent treatment; The pickling treatment is: using hydrofluoric acid and / or concentrated nitric acid with a concentration of 0.5-1.5 mol / L to clean the surface of the first ceramic layer; The silane coupling agent treatment comprises: coating the silane coupling agent on the surface of the first ceramic layer after pickling, and then curing; The silane coupling agent includes one or more of 3-methoxypropyltrimethoxysilane and isobutyltriethoxysilane; The mechanical treatment includes surface grinding, sandblasting and cleaning.

7. The method for preparing the ceramic aluminum-based silicon carbide layered composite material according to claim 1, characterized in that: In step S3, the preparation method of the aluminum-based silicon carbide slurry is: S31: placing silicon carbide, an organic plasticizer, a binder, a coupling agent, and a lubricant in a solvent to obtain a mixed solution; S32: placing the aluminum alloy powder and the dispersant in a mixed solution, and stirring at a rotation speed of 20000-30000 rpm to obtain a mixed slurry; S33: ball milling the mixed slurry to obtain aluminum-based silicon carbide slurry.

8. The method for preparing the ceramic aluminum-based silicon carbide layered composite material according to claim 7, characterized in that: In step S31, the solvent refers to polyethylene glycol and alcohol in a volume ratio of 1:(1-2); and / or, the mass ratio of silicon carbide to solvent in step S31 is 1:(3-5); And / or, in step S33, the weight ratio of the mixed slurry to the grinding balls is 1:(8-10), and the ball milling time is 3-20 hours.

9. The method for preparing the ceramic aluminum-based silicon carbide layered composite material according to claim 1, characterized in that: The thickness of the first ceramic layer is 20-30 μm; And / or, the thickness of the aluminum-based silicon carbide layer is 10-20 μm; And / or, the second ceramic layer has a thickness of 20-30 μm.

10. A ceramic aluminum-based silicon carbide layered composite material obtained by the method for preparing a ceramic aluminum-based silicon carbide layered composite material as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Three-dimensional overlapped laminar composite ceramic coating and preparation method thereof

    CN104557054A

  • Corrosion-resistant and wear-resistant piston rod based on silicon carbide coating and preparation method thereof

    CN112322096A